Seashells : more than a home - Stewart, Melissa; Brannen, Sarah S. (2019)
"This book sheds a surprising light on how seashells--the hard, protective outer layer that mollusks inhabit--serve tremendous purpose. This large group of marine animals needs shells for protection, feeding, transportation, anchorage, and more."--
Includes bibliographical references
Ages 6-9
Keywords: Mollusks -- Juvenile literature; Shells -- Juvenile literature; Instructional and educational works; Picture books